(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to investigate in detail the function of Instagram social media in improving the quality of customer service at PT PLN (Persero), especially at the Palembang Customer Service Implementation Unit (UP3). In today's digital era, social media plays a role as an important communication channel that is not only used for promotion, but also as a place for complaints and education for the public. By applying a descriptive qualitative method, this study analyzed the Instagram account @plnup3palembang for the period between January and April 2025. Data were obtained through observations of posting activities, content documentation, and casual interviews with customer service staff and PLN social media managers. The results of the study show that Instagram plays a role as an efficient information channel, a tool for providing quick responses to consumer complaints, and a medium for creating a positive image and disseminating knowledge about electrical safety. The researcher concluded that the communication approach through Instagram has a significant impact on customer satisfaction and encourages digital public engagement with the company.